2012
DOI: 10.1093/annonc/mdr432
|View full text |Cite|
|
Sign up to set email alerts
|

Adverse events risk associated with bevacizumab addition to breast cancer chemotherapy: a meta-analysis

Abstract: Bevacizumab did increase the risk of LVD and hemorrhagic events. The addition of bevacizumab to chemotherapy in patients with metastatic breast cancer was not associated with a significant increase in grade ≥ 3 arterial or venous thromboembolic events, GI perforation, or fatal events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
1
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 25 publications
6
24
1
2
Order By: Relevance
“…An increased incidence of cardiac events with decreases in left ventricular ejection fractions have been noted in other bevacizumab trials and particularly in trials in which anthracyclines have been combined with bevacizumab. [29][30][31][32] There are data from our trial as well as the literature that the decrease in LVEF may be reversible though the percentage who completely recover function, and the risk factors for left ventricular dysfunction are currently unknown. In our trial, the median age in patients with grade 2 or higher LVEF dysfunction was 68 years, the same as in our entire study group.…”
Section: Discussionmentioning
confidence: 91%
“…An increased incidence of cardiac events with decreases in left ventricular ejection fractions have been noted in other bevacizumab trials and particularly in trials in which anthracyclines have been combined with bevacizumab. [29][30][31][32] There are data from our trial as well as the literature that the decrease in LVEF may be reversible though the percentage who completely recover function, and the risk factors for left ventricular dysfunction are currently unknown. In our trial, the median age in patients with grade 2 or higher LVEF dysfunction was 68 years, the same as in our entire study group.…”
Section: Discussionmentioning
confidence: 91%
“…While not active in melanoma (23), pan- creatic cancer (24,25), and prostate cancer (26), they have shown some effectiveness when combined with cytotoxic therapy in nonsmall cell lung cancer (27)(28)(29) and colorectal cancer (30), while the benefit in breast cancer remains controversial (31)(32)(33)(34). Among the main problems with these drugs are toxicity and rapid acquired resistance (35,36). In the present study, we showed that disruption of the interaction of RAS with PI3K p110α in host tissue impaired tumor-induced angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of bevacizumab described here must be balanced with its adverse event profile. A meta-analysis of five randomized trials [5] showed the following to be more common when bevacizumab was added to chemotherapy in the treatment of breast cancer (all differences were statistically significant): proteinuria (odds ratio [OR], 27.68), hypertension (OR, 12.76), left ventricular dysfunction (OR, 2.25), and hemorrhagic events (OR, 4.07). Although these adverse events have the potential to cause complications, most patients do not seem to have a negative impact on their quality of life (QOL) with the addition of bevacizumab, and in the same meta-analysis there were no statistically significant differences for gastrointestinal perforation, vascular events, fatal events, or febrile neutropenia.…”
mentioning
confidence: 99%